The COVID-19 pandemic: how to maintain a healthy immune system during the lockdown – a multidisciplinary approach with special focus on athletes - Yousfi, Narimen; Bragazzi, Nicola L.; Briki, Walid; Zmijewski, Piotr; Chamari, Karim (Biology of Sport, 2020)
On January 31, 2020, the World Health Organization (WHO) declared the outbreak of a novel coronavirus responsible for an infection termed COVID-19 as a global public health emergency. To slow the spread of the coronavirus, countries around the world have been implementing various measures, including school and institutional closures, lockdown and targeted quarantine for suspected infected individuals. More than a third of the world’s population have been home confined less than 4 months after the start of the outbreak. The present article aims to advise healthy individuals and athletes who are in lockdown regarding their lifestyle in order to keep healthy, safe and fit. The advice contained in the present article could apply to anyone aiming at remaining in good physical and mental health while forced to undergo lockdown, quarantine, or limited movement (movement control order). Boosting the immune system is crucial during such periods for confined people and especially for confined athletes. Specific recommendations must be followed concerning boosting the immune system through physiological and psychological management. This article analyses the available scientific evidence in order to recommend a practical approach, focusing on nutrition, intermittent fasting or caloric restriction, vitamin D insufficiency, sleep pattern, exercise, and psychodynamic aspects as factors impacting the immune system and human health in general.